PENYELESAIAN SENGKETA MEDIS DI INDONESIA - Dhea Nisa Arinanda; Miranda Aurelia; Chelsia Salsa Bernadita (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Health is an important and fundamental thing in human life. Everyone will make a positive and beneficial contribution to life if they are in a healthy condition. Health development aims to improve the level of public health through increasing health efforts, health financing, human resources and medicines. Laws for health develop along with the development of the health service sector and are considered an increasingly necessary element in maintaining balance, maintaining and improving everyone's health status. Sometimes the relationship between doctors and patients does not always go well. Sometimes the patient's hope of recovering from the disease they suffer from does not come true and can even worsen their physical condition or even lead to death. Furthermore, advances in technology and the increasing criticality of society towards the medical services they receive have led to a reduction in the knowledge gap between patients and doctors and an increasing openness to judgment and criticism. So there are also many medical disputes that occur in Indonesia. Therefore, this research contains the process of resolving medical disputes in Indonesia which can be carried out through professional and non-professional institutions. Non-professionalism can be resolved outside of court (non-litigation) and in court (litigation).